Pengaruh Kecerdasan Emosional Terhadap Penilaian Hasil Belajar Akuntansi Pada Mahasiswa Konsentrasi Akuntansi BP 2010 di Sekolah Tinggi Keguruan Dan Ilmu Pendidikan (STKIP) PGRI Sumatera Barat - Duana, Dina Putri; Susanti, Nora; Eprilison, Vivina (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This research has a background by less. It is caused by lock of studentâs emotional intelligence in the learning process. The research aims to know significant contribute of emotional intelligence of student, consist of self introduction, self control, motivation, emphaty, and social skill to result study of studentÂ  accountancy in studentâs accountancy academic years 2010. For, hyphothesis testing was used t test by using SPSS 15.0 version.Â  Based on result of analyze data got self introduction have significant contribute to result study of accountancy on studentâs accountancy academic years 2010 in STKIP PGRI Sumatera Barat, self control have significant contribute to result study of accountancy on studentâs accountancy academic years 2010 in STKIP PGRI Sumatera Barat, Motivation have significant contribute to result study of accountancy on studentâs accountancy academic years 2010 in STIKP PGRI Sumatera Barat. Emphaty have significant contribute to result study of accountancy on studentâs accountancy academic years 2010 in STIKP PGRI Sumatera Barat, and social skill have significant contribute to result study of accountancy on studentâs accountancy academic years 2010 in STIKP PGRI Sumatera Barat.